Management of Myelomeningocele in Namibia - Sallah, Aminata (Division of General Surgery, 2026)
There is a lack of information on the surgical management of myelomeningocele (MMC) in Namibia. We had three objectives (1) Determine the occurrence of Spina Bifida (SB) in Namibia from 2017 to 2021, (2) Determine the management and outcomes of babies born with MMC/SB, (3) Determine the extent of multi-disciplinary team engagement in the management of MMC and referrals in hospital and at discharge. Methodology: This was a retrospective observational study conducted in Windhoek, Namibia from 2017 to 2021 at Windhoek Central Hospital (WCH) and Katutura Intermediate Hospital (KIH). Data was collected from theatre books and patient files. Records of the MMC affected patients were collected and analysed, including demographic and peri- and post-operative care records. Results: 27 cases were operated during the 5 year study period, 15 (55.6%) and 12 (44.4%) from KIH and WCH respectively. Average age of operation were mean 7.61months , median 7.0 months (range 0.07-24 months), 15 (55.6%) of the patients were female. Mode of delivery was available in 3 (11.1%) of cases, with 2 (66.7%) normal deliveries and 1 (33.3%) caesarean section. Majority of the cases with origin reported were from Oshakati, 6 (55.5%) followed by Keetmanshoop, Mariental and Windhoek which each contributed 2 (13.3%) cases. With regard to regional distribution, reported and combined, North and South regions contributed the most, at 8 (53%) and 4 (26.6%) patients respectively. Myelomeningocele repair operations were 19 (70.3%)followed by Myelomeningocoele plus Shunt insertion (hydrocephalus) 5 (18.5%). The average operating time duration reported for all the operations (20 patients )was 181.5 minutes (Range 75-400 minutes), for MMC only operation (12 patients) was 136.4 minutes (Range 75-230 minutes). The location of the MMC was only reported on in 7 (25.9%) cases. Complications or none were reported on in 9 (33.3%) of the total cases, with 4 (44.4%) experiencing complications or 14.8% of the total. Anaemia was reported in 2 (22%) difficulty passing urine in 1 (11.1%) and septic wound in 1 (11.1%) of the cases. There were records of multi-disciplinary referral in only 2 (7.4%) of the total patients in files. There is no report on the extent of folate fortification in the Namibian diet. Discussion/Conclusion In this study of the management of MMC in Namibia, we described demographics, management, captured gaps and limitations. The age of repair needs to be improved upon to approach international gold standards of 72 hours. Operating time is close to worldwide averages. Postnatal management is substantially more expensive than prevention of MMC. Food fortification information was not readily available. A national strategy to close gaps will improve both prevention and management, from preconception through postnatal and lifelong MMC care in Namibia.